Knowledge and attitude towards palliative care among undergraduate nursing students at Universiti Sains Malaysia (USM) - Join, Erra Venessa (Universiti Sains Malaysia, 2024)
This study investigates the knowledge and attitudes toward palliative care among final-year undergraduate nursing students at Universiti Sains Malaysia (USM). Understanding the level of knowledge and attitudes of nursing students is crucial for improving palliative care education and ensuring that future nurses are well-prepared to provide compassionate and effective end-of-life care. The purpose of this study is to identify the knowledge and attitudes of these students regarding palliative care, aiming to inform and enhance the nursing curriculum at USM. A descriptive cross-sectional design was employed, involving a purposive sample of 130 final-year undergraduate nursing students from the Health Campus of USM. Participants completed a 50-item survey evaluating their understanding and perspectives on palliative care. The results indicated that 13.1% of students had good knowledge, 81.5% had moderate knowledge, and 5.4% had poor knowledge of palliative care. Regarding attitudes, 29.2% displayed a positive stance, while 70.8% were neutral; no negative attitudes were reported. A significant positive correlation (r=0.332, p<0.000) was found between knowledge and attitudes, suggesting that enhanced education could improve attitudes toward palliative care among nursing students. These findings underscore the need for targeted educational interventions within the nursing curriculum to better prepare students for delivering high-quality palliative care. Revising current educational modules to include comprehensive coverage of both theoretical knowledge and practical skills in palliative care is essential to meet the growing demand for effective palliative care services in Malaysia and ensure that nursing graduates are well-equipped for their roles.